How to perform ablative laser surgery for skin resurfacing? - Ercan Çalışkan; Ayşenur Botsalı (Galenos Publishing House, 2022)
The target chromophore of ablative lasers is water.The ablative lasers in dermatologic practice include carbon dioxide (CO2) and Erbium: yttrium-aluminium-garnet (YAG) lasers. Their different physical properties determine the ablation zone and accompanying thermal damage within the skin. Fractional laser technology was a major step through the evolution of ablative lasers decreasing the down-time period and complications of the interventions. Strict concordance with the preoperative and postoperative recommendations is central to minimize the risks and complications of the interventions. Our intention with this review is to reveal the basic principles of ablative lasers and to illustrate the various indications depending on the physician's creative potential.